Brent Working Women's Charter Campaign, 1974 (1974)
1974 1960-2000 "Brent Working Women's Charter Campaign, 1974" [EP0121a], 1974 The Working Women's Charter was launched by the London Trades Council in March 1974, but was given force by local charter campaign groups established around the country. This article from the November 1974 issue of Brent Hard Times describes some of the activities of a group based in the London Borough of Brent and includes the ten points of the original Charter.